Obesity-associated cardiometabolic complications in polycystic ovary syndrome: The potential role of sodium-glucose cotransporter-2 inhibitors - Pruett, Jacob E.; Romero, Damian G.; Yanes Cardozo, Licy L. (Frontiers in Endocrinology, 2023)
Polycystic Ovary Syndrome (PCOS) is the most common endocrine disorder in reproductive-age women. PCOS is characterized by androgen excess, oligo/anovulation, and polycystic appearance of the ovaries. Women with PCOS have an increased prevalence of multiple cardiovascular risk factors such as insulin resistance, hypertension, renal injury, and obesity. Unfortunately, there is a lack of effective, evidence-based pharmacotherapeutics to target these cardiometabolic complications. Sodium-glucose cotransporter-2 (SGLT2) inhibitors provide cardiovascular protection in patients with and without type 2 diabetes mellitus. Although the exact mechanisms of how SGLT2 inhibitors confer cardiovascular protection remains unclear, numerous mechanistic hypotheses for this protection include modulation of the renin-angiotensin system and/or the sympathetic nervous system and improvement in mitochondrial function. Data from recent clinical trials and basic research show a potential role for SGLT2 inhibitors in treating obesity-associated cardiometabolic complications in PCOS. This narrative review discusses the mechanisms of the beneficial effect of SGLT2 inhibitors in cardiometabolic diseases in PCOS.